Exosomal miR-93-3p targets EIF4EBP1 to regulate macrophage polarization and accelerate wound healing post-anal fistula surgery - Zhang, Wei; Feng, Wenzhe; Chen, Junhong; Cao, Ruoxi; Chen, Xi (Frontiers in Pharmacology, 2025)
BackgroundDelayed wound healing following anal fistula (AF) surgery remains a clinical challenge. This study endeavors to identify and validate key exosomal miRNAs that regulate postoperative inflammation after AF surgery by integrating multi-omics analyses with functional assays, and to elucidate the molecular mechanisms by which these miRNAs and their target genes influence macrophage M1/M2 polarization.Methods15 patients undergoing AF surgery were randomized to three groups. The negative control group received sterile Vaseline gauze dressings, the positive control cohort took Kangfuxin Solution, and the treatment cohort received Wugu Qilin Ointment. Wound exudates were collected postoperatively and exosomes were isolated via ultracentrifugation. Total RNA was extracted through the TRIzol method, followed by miRNA microarray analysis to identify differentially expressed miRNAs (DEMs). Candidate miRNAs were validated via qPCR to identify those significantly linked to the therapeutic efficacy of the traditional Chinese medicine (TCM) method of Euriching Pus for Tissue Growth. In vitro, the differentiation of THP-1 cells into macrophages was employed via PMA. The MP were verified by flow cytometry (FC), qPCR and Western blotting (WB). Potential miRNA target genes were predicted using TargetScan before Gene Ontology (GO) functional annotation and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analysis. The direct interplay between miRNA and its target gene was verified through a dual-luciferase reporter (DLR) assay.ResultsMicroarray analysis and qPCR validation identified miR-93-3p as the most significantly DEMs. miR-93-3p overexpression markedly downregulated M1 macrophage marker CD86 and pro-inflammation cytokines IL-1β, IL-6, and TNF-α, while upregulating M2 markers Arg-1, CD206, and anti-inflammation cytokines IL-10 and TGF-β in functional assays. Conversely, miR-93-3p suppression exhibited the opposite effect. WB analysis confirmed that miR-93-3p bidirectionally regulated CD86, Arg-1, and CD206 protein expression. Bioinformatic analysis suggested that miR-93-3p possibly targets EIF4EBP1, thereby modulating biological processes like inflammatory response, cellular metabolism, and MP. This regulatory relationship was unveiled through DLR assays, proving that miR-93-3p specifically suppresses EIF4EBP1 expression.ConclusionThis study is the first to elucidate the molecular mechanism by which the TCM therapeutic approach of Euriching Pus for Tissue Growth promotes M2 MP through the exosomal miR-93-3p/EIF4EBP1 axis, and theoretically supports the formulation of new exosome-based miRNA treatment strategies for postoperative anti-inflammatory treatment in AF.